Gambaran Penggunaan Obat Tradisional di Kecamatan Wongsorejo Kabupaten Banyuwangi (PROFESSIONAL HEALTH JOURNAL, 2023)
Therapy with traditional medicine is still an option for Indonesian, including Banyuwangi. The herbal shop in Banyuwangi is still an option for therapy. This research aimed to get an overview of the traditional medicine in Wongsorejo village, Banyuwangi. This research was observational, with a cross-sectional study design and a questionnaire as the research instrument. This research was attended by 67 respondents who met the inclusion criteria. The research results stated that the information source for using herbal medicine was the family (53.73%); the average use of traditional medicine was 1-5 years (59.7%), with an average use of once a week (86.57%). Respondents liked the concoctions prepared by traditional drug dealers (52.24%), but these traditional medicines only had a temporary effect of 76.12%. Respondents who had consumed the given capsule (59.7%) were two capsules (55.22%). These traditional medicines are most often used to treat musculoskeletal pain (71.64%), and the therapeutic effect is felt between 1 to 5 hours after taking the traditional medicine (77.61%) and states better after consuming these traditional medicines (95.52%). Based on these data, it can be concluded that to treat complaints of rheumatic pain and its used together with capsules given by herbal medicines seller.